# Thread: quotent rule for natural logs

1. ## quotent rule for natural logs

f(x) = (lnx)x
f'(x) = x * (lnx)' - (lnx) * x'/(x)^2
f'(x) = x*(1/x) - (lnx)*1/(x)^2
f'(x) = 1 - lnx/(x)^2

I hope this is correct

2. Originally Posted by becky
f(x) = (lnx)x
f'(x) = x * (lnx)' - (lnx) * x'/(x)^2
f'(x) = x*(1/x) - (lnx)*1/(x)^2
f'(x) = 1 - lnx/(x)^2

I hope this is correct
it's not correct i'm afraid. you would use the product rule here, since you don't have a quotient (or did you mean to type a slash after the lnx but forgot?)

y = (ln)x
=> y' = lnx + x(1/x) = lnx + 1

3. Was this what you meant? If so, you were correct (though you need to have parenthesis in your answer to show that this is the same thing)

4. ## Inx/x

Yes, that's what the problem...
Glad you caught my mistake in writing the problem, I probably wouldn't have and would really be confused right now...
Yeah, I got it right!

5. Originally Posted by becky
Yes, that's what the problem...
Glad you caught my mistake in writing the problem, I probably wouldn't have and would really be confused right now...
Yeah, I got it right!
Good Job

so you understand it well now?

why not try a few more problems and post your solutions

6. ## Re:

Jhevon's is correct, but I think he will agree that unless you are told to do so using the Quotient rule isn't the easiest way to solve this problem...

Re: